Application of Stream Conductivity to Activity of Potential Large-Scale Landslide - Tsai, Yuan Jung; Chen, Yi Jing; Weng, Chieh Hsuan; Syu, Fang Tsz; Hsu, Kun-An; Lee, Wei Lin (Frontiers in Earth Science, 2022)
Underclimate changes, extreme rainfall events can cause catastrophic sediment-related disasters such as large-scale landslides. To work on disaster prevention, the government has investigated the location of potential large-scale landslides by a geological and geomorphological approach. However, the activity of potential large-scale landslides has to rely on expensive on-site monitoring system, for example, observed drill hole of groundwater and underground displacement. Recently, the variation of stream electronic conductivity has been proposed to investigate the activity of large-scale landslide in Japan. Therefore, this study applied this concept in Taiwan. First, the temporal and spatial variations of stream electronic conductivity near the potential large-scale landslide have been surveyed. Accordingly, an interesting finding is that the spring water from the potential large-scale landslide can increase the concentration of chemical ion, and thus, the value of stream electronic conductivity increases. Second, the comparison of rainfall data, stream electronic conductivity, and ground surface displacement has been analyzed. There is a sound agreement between stream electronic conductivity and ground surface displacement. This result implied that stream electronic conductivity could be a possible index to monitoring the activity of potential large-scale landslides indirectly.